Low density polyethylene/silica nanocomposite foams. Relationship between chemical composition, particle dispersion, cellular structure and physical properties. (August 2016) - Laguna-Gutierrez, Ester; Saiz-Arroyo, Cristina; Velasco, Jose I.; Rodriguez-Perez, Miguel A.
Graphical abstract: Highlights: Structure and properties of solid and foamed LDPE/silica composites are analyzed. The use of a compatibilizer does not contribute to increase silica dispersion. The silica nucleating effect is mitigated by the compatibilizer. Silica particles lead to an overall increase in mechanical response. Synergistic effects are detected in the mechanical behavior of the foamed materials. Abstract: This paper presents the production and characterization of polymeric nanocomposite foams based on low density polyethylene (LDPE) and different contents of silica nanoparticles. The properties of these foamed materials are conditioned by the properties of the polymer matrix and by the characteristics of the cellular structure. In general, when adding nanoparticles several improvements are obtained in both the solid nanocomposite and the cellular structure. However, the achievement of these potential improvements is conditioned by the level of filler dispersion and by the compatibilization degree between the particles and the polymer. This work analyzes the effects on the dispersion and compatibilization levels of adding, or not, a compatibilizer agent (linear low density polyethylene grafted with maleic anhydride, LLDPE-g-MA), with the aim of understanding the structure and properties of the foamed materials produced from these composites. A modified version of the pressure quench method was used to produce the foamed samples. This method allows obtaining net-shaped foams adequate for analyzing both their microstructure and mechanical properties. Results show that for this particular system, the incorporation of the LLDPE-g-MA compatibilizer does not promote a better dispersion but implies significant differences in terms of nucleating efficiency and reinforcing effect of the nanoparticles. While for solid nanocomposites the higher degree of bonding polymer/nanoparticle promoted by the presence of the compatibilizer translates into a positive mechanical reinforcing effect, for foamed nanocomposites, such high level of compatiblization mitigates the nucleating effect of the nanoparticles. This translates into poorer mechanical properties in the foamed samples containing the compatibilizer agent.